Opini Publik Tentang Nuansa Islam dalam Praktik Periklanan di Indonesia - Mandjusri, Alma (Universitas Al Azhar Indonesia, 2023)
The emergence of Islamic lifestyle trends in Indonesian Muslim society, gave rise to advertising strategies with religious nuances. Various product advertisements include halal logos, use religious attributes, and even use religious figures as brand ambassadors. Religious nuances in advertising practices in various media, both print, electronic and digital in Indonesia have raised opinions on the pros and cons among advertising industry players. This research uses a case study method with a descriptive qualitative approach to analyze the opinions of advertising industry players regarding the use of religious nuances, symbols and religious attributes in advertising practice, an issue that occurs in people's lives that continues to develop. After analyzing data from the interview results regarding the use of Islamic nuances in advertising practices in Indonesia based on the grouping of seven perspectives by Glynn, Ostman, and McDonald (2018), the opinions of informants, can be mapped into three groups, namely opinion groups with a Looking-glass perception perspective; Pluralistic ignorance and The third-person effect.